2009
DOI: 10.1507/endocrj.k09e-172
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Efficacy and Safety of Octreotide LAR in Japanese Patients with Acromegaly: Shizuoka Study

Abstract: Abstract. The efficacy and safety of the long-acting repeatable formulation of octreotide (OCT-LAR) treatment in patients suffering from acromegaly was investigated retrospectively in Shizuoka prefecture, Japan. Thirty patients (11 male, 19 female; average age, 48.9 years old), 29 of whom had undergone transsphenoidal surgery previously, were treated with OCT-LAR. OCT-LAR was injected i.m. every 4 weeks with an intended protocol of 20 mg over 24 months, however, 46.7% of patients required the dose of OCT-LAR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…are similar to those of a study on octreotide LAR in Japanese patients with acromegaly [19]. Sub-analysis results stratified according to the presence or absence of prior treatment with octreotide and dopamine agonist showed similar efficacy of lanreotide Autogel regardless of the type of pretreatments.…”
Section: ) Safetysupporting
confidence: 80%
“…are similar to those of a study on octreotide LAR in Japanese patients with acromegaly [19]. Sub-analysis results stratified according to the presence or absence of prior treatment with octreotide and dopamine agonist showed similar efficacy of lanreotide Autogel regardless of the type of pretreatments.…”
Section: ) Safetysupporting
confidence: 80%
“…There are a number of drugs available for the treatment of acromegaly such as SSAs, dopamine agonists, and growth hormone receptor antagonist [2]. Clinical data supporting efficacy and safety of first-generation SSAs, long-acting octreotide [21] and lanreotide Autogel [22], in Japanese patients with acromegaly have previously been reported. In most of the studies, the response rate in patients treated with first-generation SSAs ranges from 17% to 41% [2,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“… 32) A study of Japanese patients also showed the same results. 33) In those patients, the alternative or additional therapies may be required. Common but transient side effects include nausea, white stool, abdominal discomfort, and diarrhea.…”
Section: Acromegalymentioning
confidence: 99%